Productivity and Organization in Portuguese Firms - Lorenzo Caliendo; Giordano Mion; Luca David Opromolla; Esteban Rossi-Hansberg (Center for Economic Studies and ifo Institute (CESifo), 2015)
The productivity of firms is, at least partly, determined by a firm's actions and decisions. One of these decisions involves the organization of production in terms of the number of layers of management the firm decides to employ. Using detailed employer-employee matched data and firm production quantity and input data for Portuguese firms, we study the endogenous response of revenue-based and quantity-based productivity to a change in layers: a firm reorganization. We show that as a result of an exogenous demand or productivity shock that makes the firm reorganize and add a management layer, quantity based productivity increases by about 4%, while revenue-based productivity drops by more than 4%. Such a reorganization makes the firm more productive, but also increases the quantity produced to an extent that lowers the price charged by the firm and, as a result, its revenue-based productivity.
Keywords: D22; D24; L23; F16; J24; J31; 330